Identitas kepemilikan pura dalam hubungan dengan perkembangan pariwisata dan konflik sosial di Bali - GPB Suka Arjawa (Faculty of Social and Political Science, Universitas Airlangga, 2014)
Social conflict in Bali frequently involves public prayer area (Pura), can last in several days and leads to disputes between family within same community. Therefore, the community who perform prayer in the Pura was prone to disengagement caused by conflict. The purpose of this article was to understand the relations between social conflict in Bali which related to ownership social identity and tourism development in Bali. The research method used to approach was conducted in qualitative way in order to shows positive correlations between social changes and the conflicts. The social change in Bali was caused by economic factor to the social tradition factor, directly faced with identity in each community which have responsibility to protect the temple. Tourism is the basic factor for the social change in Bali. Tourist industry make the existence of hotel and restaurant increased. By the local goverment, the tax of these hotel and restaurant were allocated a fund for desa pakraman, the locus of cultural tourism in Bali. But in any cases, most of community members in desa pakraman make a decision to use this fund to develop the temple. Different opinion in community to use this fund could cause a conflict because the community in this temple has different identity.